Anti-Icing Property of Superhydrophobic Nanostructured Brass via Deposition of Silica Nanoparticles and Nanolaser Treatment - Saqib Hussain; Tanyakorn Muangnapoh; Bhawat Traipattanakul; Milin Lekmuenwai (Nanomaterials, 2023)
Ice accumulation on brass surfaces can lead to heat transfer inefficiency, equipment degradation, and potential accidents. To address this issue, superhydrophobic surface technology is utilized. This work aims to develop superhydrophobic nanostructured brass surfaces using the combination of nanolaser ablation and the deposition of silica nanoparticles to achieve the anti-icing property. Four distinct types of brass surfaces namely, the bare surface (BS), the lasered surface (LS), the coated surface (CS), and the coated-lasered surface (CLS) were prepared. The anti-icing performances of the fabricated samples including the effects of the surface structure, the droplet size, and the surface temperature were investigated and evaluated. The results showed that the delayed icing time increased with the increases in the apparent contact angle, the droplet size, and the surface temperature. When the apparent contact angle increased, the contact area between the droplet and the cooling substrate reduced, leading to the longer delayed icing time. With the deposition of silica nanoparticles and nanolaser treatment, CLS achieved the greatest apparent contact angle of 164.5°, resulting in the longest delayed icing time under all experimental conditions. The longest delayed icing time on CLS recorded in this study was 2584 s, which was 575%, 356%, and 27% greater than those on BS, LS, and CS, respectively. The study also revealed that the surface structure played a more crucial role in achieving the anti-icing property when compared to the surface temperature or the droplet size. The shortest delayed icing time on CLS at the lowest surface temperature and at the smallest droplet size was longer than those on BS and LS at all conditions. The results were also discussed in relation to a heat transfer model. The findings of this research can serve as an avenue for advancing knowledge on heat transfer enhancement and energy efficiency.